PERSONALITY TYPE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT. BALI REGIONAL DEVELOPMENT BANK, BADUNG BRANCH - Wijaya, Gede Crisna; Wulandari, Ni Made Tia (LPPM Univ. Ibn Khaldun Bogor, 2023)
In achieving the main goals of a company, competent HR plays an important role in it, but considering that every HR owned by the company has a different personality and level of discipline, of course, this difference will greatly affect the performance of the employees themselves which will result in achieving or whether or not a company goal. PT. The Regional Development Bank of Bali Badung Branch always tries to provide satisfaction to its customers by providing the best service and in accordance with what customers want and providing very high quality service products. Personality Type and Employee Work Discipline are very influential on Employee Performance to achieve the company's goals PT. Regional Development Bank Bali Badung Branch, but there are several problems related to the many types of personalities and lack of discipline of employees when carrying out their work which affects employee performance such as employees who have difficulty communicating with co-workers and leaders, bringing down fellow co-workers and being less open to things. -new things are also delays and violations committed. So to improve employee performance, HR Manager is expected to be able to take appropriate action so that the company's performance continues well.